Short‐Channel Vertical Organic Field‐Effect Transistors with High On/Off Ratios. (2nd April 2019) - Dogan, Tamer; Verbeek, Roy; Kronemeijer, Auke J.; Bobbert, Peter A.; Gelinck, Gerwin H.; van der Wiel, Wilfred G.
Abstract: A unique vertical organic field‐effect transistor structure in which highly doped silicon nanopillars are utilized as a gate electrode is demonstrated. An additional dielectric layer, partly covering the source, suppresses bulk conduction and lowers the OFF current. Using a semiconducting polymer as active channel material, short‐channel (100 nm) transistors with ON/OFF current ratios up to 10 6 are realized. The electronic behavior is explained using space‐charge and contact‐limited current models and numerical simulations. The current density and switching speed of the devices are in the order of 0.1 A cm −2 and 0.1 MHz, respectively, at biases of only a few volts. These characteristics make the devices very promising for applications where large current densities, high switching speeds, and high ON/OFF ratios are required. Abstract : A novel vertical organic field‐effect transistor geometry is demonstrated addressing the short‐channel effect, in particular by suppressing the undesired bulk current. An insulating layer on top of the bottom contact forces injection of the charge carriers only from the sides of the bottom metal and current flow within a thin layer close to the gate dielectric.